學以致用中文課程（演講）對疑似中文資優學生中文素養提升之研究 ——以澳門某中學高中學生為例 =: A Study On The Improvement Of Chinese Literacy Of Suspected Gifted Chinese Students In The Course Of Learning-to-Use Chinese (Speech) – Taking Senior High School Students Of A Middle School In Macau As An Example - O, Chi Wa (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 中文素養; 學以致用中文課程; 演講; 疑似中文資優; 資優教育

將CRA教學法融入澳門小學融合班數學課程 之行動研究-以二年級兩位數減法單元為例 =: An Action Study of Integrating Concrete-to-Representational-to-Abstract (CRA) into the Mathematics Learning of Integrated Classes in Macao Primary Schools - Taking the Two-digit Subtraction Unit of Grade 2 as an Example Concrete-to-Representational-to-Abstract (CRA) - Zhuang, YanYan (University of Saint Joseph, 2023)
Keywords: CRA教學策略; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 兩位數减法; 小學數學課程; 融合生; 行動研究

The Collaboration and Challenges Faced by Therapists within Professional Inclusive Education Teams in Macau =: 澳門治療師在融合教育專業團隊中的合作情況及挑戰 - Lao, Pek San (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作模式; 團隊合作; 治療服務; 澳門治療師

澳門普通班教師與資源教師合作教學現況與改進建議之個案研究 =: A CASE STUDY OF CO-TEACHING PRACTICES AND IMPROVEMENT SUGGESTIONS AMONG GENERAL EDUCATION TEACHERS AND RESOURCE TEACHERS IN MACAO - Lai, Chong Weng (University of Saint Joseph, 2023)
Keywords: Inclusive education; Resource teacher; Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 合作教學; 澳門; 融合教育; 資源教師

澳門小學非特教專業教師對融合教育之態度研究 =: A study on the Attitudes of the Non-specialized Teachers of Primary Schools in Macau towards Inclusive Education - Ng, Ka Man (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 小學; 融合教育; 非特教專業教師

澳門私立融合教育學校中資源教師現況與問題之研究 =: A RESEARCH STUDY ON THE CURRENT SITUATION AND FACING PROBLEMS OF RESOURCE TEACHERS IN PRIVATE INCLUSIVE EDUCATION SCHOOLS IN MACAO - Chan, Lok In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門; 私立融合教育學校; 融合教育; 資源教師

澳門融合教育下資源老師心路歷程之質性研究 =: A QUALITATIVE STUDY ON THE SPIRITUAL JOURNEY OF RESOURCE TEACHERS IN INCLUSIVE EDUCATION IN MACAO - Ke, Li Ping (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 心路歷程; 融合教育; 資源老師; 質性研究

澳門幼稚園非特教專業教師在融合教育班級經營的困難與應對策略之研究 =: Challenges and Strategies in the Management of Integrated Education Classes: Insights from Non-certified Kindergarten Special Education Teachers in Macau - Leong, Choi Cheng (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 澳門幼稚園; 班級經營; 融合教育; 非特教專業教師

INTEGRATING ROBOTS INTO READING IN AN INCLUSIVE ESL CLASSROOM AT LOWER PRIMARY - Lei, Ut Wa (University of Saint Joseph, 2023)
Establishing and improving the independent reading ability of middle school students has become one of the critical topics in the world, especially for second language learners. The cultivation of independent reading ability has specific challenges. This action research investigated the effectiveness of integrating robot-assisted teaching in reading lessons at lower primary grades. A group of third-grade students (n=15) participated in this research. The instruments include the pre-and post-test of a reading competency test (RCT) and motivational index (MI), a teacher reflection journal, and focus group discussion with parents. The whole intervention is conducted in two cycles, and requires the completion of four 40-minute lessons each week per cycle. The findings support the view that integrating robot-assisted teaching in the classroom can improve students' learning motivation to a certain extent, and that intervention programs positively impact students' learning motivation and independent reading ability in English. This study provides suggestion for the design of English reading instruction, and encourages English teachers to pay more attention to improving students' independent reading ability
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; independent reading skills; learning motivation; robot-assisted teaching

探討教師及家長視角下澳門推行生命教育之現況 =: EXPLORING THE CURRENT SITUATION OF LIFE EDUCATION IN MACAU FROM THE PERSPECTIVES OF TEACHERS AND PARENTS - Lei, Choi In (University of Saint Joseph, 2023)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph; 教師自我效能; 生命教育; 親社會行為